On the biodiversity and biodeteriogenic activity of microbial communities present in the hypogenic environment of the Escoural Cave, Alentejo, Portugal - Caldeira, A (2022)
Hypogenic caves represent unique environments for the development of specific microbial communities that need to be studied. Caves with rock art pose an additional challenge due to the fragility of the paintings and engravings and to microbial colonization which may induce chemical, mechanical and aesthetic alterations. Therefore, it is essential to understand the communities that thrive in these environments and to monitor the activity and effects on the host rock in order to better preserve and safeguard these ancestral artforms. This study aims at investigating the Palaeolithic representations found in the Escoural Cave (Alentejo, Portugal) and their decay features. These prehistoric artworks, dating back up to 50,000 B.P., are altered due to environmental conditions and microbial activity inside the cave. Microbial cultivation methods combined with culture-independent techniques, biomarkers’ viability assays and host rock analysis allowed us to better understand the microbial biodiversity and biodeteriogenic activity within the hypogenic environment of this important cave site. This study is part of a long-term monitoring program envisaged to understand the effect of this biocolonisation and to understand the population dynamics that thrive in this hypogean environment.